2019
DOI: 10.1039/c8pp00300a
|View full text |Cite
|
Sign up to set email alerts
|

Photo-polymerization properties of type-II photoinitiator systems based on 2-chlorohexaaryl biimidazole (o-Cl-HABI) and various N-phenylglycine (NPG) derivatives!

Abstract: A series of p-substituted NPG derivatives (Cl-NPG, OMe-NPG and NO2-NPG) comprising different push–pull characteristics have been synthesized and characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Hexaarylbiimidazole (HABI) derivatives, such as BCIM, are commonly used as PIs in the industrial production of DFRs [ 59 ]. However, because of their short-wavelength absorption, which is below 350 nm, and as one kind of type II PI, this kind of compound is usually used together with hydrogen donors such as NPG and longer wavelength photosensitizers such as 4,4′-bis(dimethylamino)benzophenone [ 60 , 61 , 62 ]. In this section, we found that COXEs can be used to improve the photoreactivity of the BCIM/NPG coinitiator system upon 450 nm LED irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Hexaarylbiimidazole (HABI) derivatives, such as BCIM, are commonly used as PIs in the industrial production of DFRs [ 59 ]. However, because of their short-wavelength absorption, which is below 350 nm, and as one kind of type II PI, this kind of compound is usually used together with hydrogen donors such as NPG and longer wavelength photosensitizers such as 4,4′-bis(dimethylamino)benzophenone [ 60 , 61 , 62 ]. In this section, we found that COXEs can be used to improve the photoreactivity of the BCIM/NPG coinitiator system upon 450 nm LED irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Hexaarylbiimidazoles are also characterized by a low sensitivity to oxygen, which has stimulated the industrial interest for this family of structures. [288][289][290][291] To end, the high yield of lophyl radicals i.e. 2,4,5-triarylimidazolyl radicals make these structures appealing candidates to initiate the FRP of acrylates when combined to hydrogen donor (See Scheme 6).…”
Section: Hexaarylbiimidazole Derivativesmentioning
confidence: 99%
“…Other mechanisms of photoinduced cleavage of photoinitiator, derivatives HABI have also been proposed. Their schemes with an explanation are presented in Figure 16 and Figure 17 [ 154 , 159 ].…”
Section: Commonly Used Photoinitiating Systems For Dental Applicatmentioning
confidence: 99%
“…The radical-mediated thiol-ene polymerization mechanism.Other mechanisms of photoinduced cleavage of photoinitiator, derivatives HABI have also been proposed. Their schemes with an explanation are presented inFigures 16 and 17[154,159].Materials 2020, 13, x FOR PEER REVIEW 14 of Proposed mechanism of the photolysis of the carbon-nitrogen (C-N) bond between the imidazole rings of HABI.…”
mentioning
confidence: 99%